Phytochemical & antidiarrheal activity of Nypa fruticans wurmb fruit shell - Tinni, Samia Sultana (Brac University, 2024)
This project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.